2014
DOI: 10.1111/1471-0528.12682
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression, antidepressant prescriptions, and congenital anomaly risk in offspring: a population‐based cohort study

Abstract: ObjectiveTo estimate risks of major congenital anomaly (MCA) among children of mothers prescribed antidepressants during early pregnancy or diagnosed with depression but without antidepressant prescriptions.DesignPopulation-based cohort study.SettingLinked UK maternal–child primary care records.PopulationA total of 349 127 singletons liveborn between 1990 and 2009.MethodsOdds ratios adjusted for maternal sociodemographics and comorbidities (aORs) were calculated for MCAs, comparing women with first-trimester s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
122
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(125 citation statements)
references
References 40 publications
2
122
1
Order By: Relevance
“…Recent studies have suggested that the association between SSRI and CHD may be explained by confounding [23,33,59]. A Danish healthcare database study of livebirths found a higher risk of CHD both among women exposed to SSRI in the first trimester, and those who paused SSRI use during pregnancy, suggesting confounding by underlying depression or factors Wemakor associated with depression [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have suggested that the association between SSRI and CHD may be explained by confounding [23,33,59]. A Danish healthcare database study of livebirths found a higher risk of CHD both among women exposed to SSRI in the first trimester, and those who paused SSRI use during pregnancy, suggesting confounding by underlying depression or factors Wemakor associated with depression [33].…”
Section: Discussionmentioning
confidence: 99%
“…for women with unmedicated depression, and for individual SSRIs found a significantly elevated risk only for paroxetine when compared to unmedicated depression [23]. A US health insurance database study found that in an analysis restricted to women with a diagnosis of depression, controlling for co-exposures to other medications attenuated the CHD risks [59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Renal dysplasia was more common in children born to mothers on fluoxetine, and hypospadias was most strongly correlated with citalopram. Congenital lower limb deformity was associated with exposure to paroxetine, sertraline and escitalopram [27].…”
Section: Antidepressant Use and The Risk Of Congenital Anomaliesmentioning
confidence: 99%